Safety and efficacy of basal bolus and premixed insulin intensification regimes in the management of type 2 diabetes mellitus : A 13 year narrative review of literature - Penwalla, NI; Othman, Noordin; MN, Norilyani; Nik Ahmad, Nik Nur Fatnoon (Malaysian Pharmaceutical Society, 2014)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic condition due to insulin resistance or relative insulin deficiency. Although insulin intensification regimens are commonly prescribed for the management of T2DM, there is uncertainty regarding their optimal use. We conducted a 13 Year narrative review to compare outcomes of these regimens in the treatment of T2DM. Method: We searched electronic databases (PubMed, Scopus, Proquest and Google Search), and “grey literature” from January 2000 to December 2013 to identify studies comparing insulin intensification regimens. Results: Out of 17 studies identified, we only included 10 studies specifically comparing Basal-Bolus regimens (BB) versus Pre-mixed Insulin Regimens (PM). Seven trials comparing regimens other than the studied regimens; with study duration lesser than 12 weeks; or involving Type 1 diabetes mellitus patients were excluded. The outcomes measured were divided into safety and efficacy parameters. Among the safety outcomes measured were Hypoglycemia, Weight Gain, Quality of Life (QoL), and other Adverse Events (AE). Whereas, efficacy outcomes measured were Glycosylated Haemoglobin (HbA1c), Fasting Plasma Glucose, Daily Plasma Glucose, Post Prandial Plasma Glucose, Carotid Intima Media Thickness (IMT), Adinopectin Level, 1-5-anhydroglucitol(1,5-AG),Total Daily Insulin (TDI) Dose and Cost. Mixed results were discovered among all the parameters measured favoring in between BB and PM regimens. Conclusion: We found that BB regimens showed better glycemic control especially in terms of the primary endpoint of HbAlc but at the expanse of significantly higher TDI dose, weight gain, and further increase in cost of treatment. Whereas, all other parameters measured were comparable between regimens. Locally, conventional human insulin is still the mainstay of insulin therapy in health facilities nationwide. Yet, none of the identified studies compared head-to-head human insulin in both arms. Thus, future researches comparing non-analogue insulin may be conducted to gather new evidence in the field of diabetes locally.